First records of peracarid crustaceans from the Cayo Matias Ocean Blue Hole, SW Cuba, with the description of two new species - Ortiz, Manuel; Winfield, Ignacio; Varela, Carlos (Zootaxa, 2012)
First records of peracarid crustaceans obtained from the Cayo Matías Ocean Blue Hole, southwestern Cuba, aredocumented. In addition, two new species of isopod and amphipod are herein described. Gnathia micheli n. sp. (Isopoda,Gnathiidae) and Boca normae n. sp. (Amphipoda, Aristiidae) were associated with filamentous algae at a depth of 20 m.Both represent the first report for a blue hole and the amphipod constitutes the first record of the genus for Cuba and theCaribbean Sea. Three other isopods, i.e. Gnathostenetroides sp., Cirolana parva, and Cirolana crenulitelson, and the cumacean Procampylaspis sp. are documented for the first time from the same blue hole.